Dinosaurs - Amiot, Romain; d (White Plains, New York : Peter Pauper Press, Inc., 2017)
Presents illustrated scenes of the Mesozoic Era and modern-day paleontology, in which children may search for hidden pictures. Explanatory text accompanies each scene.
Keywords: Paleontology -- Juvenile literature; Paleontology -- Mesozoic -- Juvenile literature; Dinosaurs -- Juvenile literature; Dinosaurs; Picture puzzles -- Juvenile literature